Impact of Nutritional Intervention on Health Outcomes among Children with Growth Disorders in the Ratahan Health Center Service Area, Southeast Minahasa - Hi Baco, Nurlela; Dareda, Kristine; Onsu, Jelly (AACENDIKIA: Journal of Nursing, 2025)
Children with growth disorders are those who, compared to normal children, have lower mental, intellectual, social, and emotional conditions. Meeting nutritional needs is a key factor in achieving optimal growth and development in line with genetic potential. An inappropriate dietary pattern can cause nutritional problems in toddlers, thereby hindering their growth and development. This study aimed to determine the effect of nutritional intervention on the health of children with growth disorders in the Ratahan Community Health Center working area. This research employed an experimental approach using a pre-experimental one-shot case study design. The variables included the independent variable (nutritional intervention) and the dependent variable (children’s health/nutritional status). The population consisted of 30 toddlers aged 1–5 years, with a sample of 9 toddlers determined using the Referer formula. Data were collected through questionnaires and observation sheets, processed using SPSS 26, and analyzed using a paired t-test. The results showed that respondents experienced an improvement in health status, as reflected by nutritional status, with 2 toddlers (22.2%) improving from undernourished to normal nutritional status. The study concluded that nutritional intervention had a significant effect on the health of children with growth disorders (p = 0.000), with p < α (0.005), indicating a relationship between nutritional intervention and children’s health. Recommendation: Mothers should be more proactive in preparing and providing a variety of nutritious foods to toddlers.